Implementasi Pembelajaran Pai Bagi Anak Berkebutuhan Khusus (ABK) Di SMALB Negeri Kota Pasuruan - Dianita Lutfiah Sungkar; Siti Rofisah; Mila Sofiyah; Fa’idatunnafi’ah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
PAI learning is a subject that teaches religious knowledge, based on the results of observations, analysis and interviews PAI learning is also taught by educators at Pasuruan City State High School. The method of delivering it is not much different from teaching normal children in general, only for children who have special needs the learning is simpler because it adapts to the students' conditions. Children who have these special needs are better known as children with special needs. They have limitations so that in teaching a lesson an educator needs to take an individual approach to be able to understand the character of each student.